Przeciwdziałanie praniu brudnych pieniędzy nowym obowiązkiem biegłego rewidenta - Ostojski, Wojciech (The Counteraction of Dirty Money Laundering New Duty of the Auditor, 2005)
The article introduces problems of counteraction to dirty money laundering in Poland. Initiating new EU instructions caused putting new of additional duties on auditors. The author discusses in detail procedures and consequences of new regulations applied by auditors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 171-180